Predictors of response to Infliximab in children with luminal Crohn's disease. (1st August 2014) - Grover, Zubin; Biron, Rebecca; Carman, Nicholas; Lewindon, Peter
Abstract: Objective: A significant proportion of patients with initial response to Inflximab (IFX), subsequently lose response (LOR). Multicentre paediatric studies report LOR in 33% to 50% with 3–5 year follow-up. Our retrospective study examined durability of response and predictors of LOR. Methods: From our IBD database of 185 children with CD, 65 received IFX maintenance therapy for luminal or fistulising Crohn's disease between January, 2006 and April, 2013. 47 with luminal CD ≥ 1 year follow-up after commencing IFX were included. We evaluated variables associated with response and describe outcomes on those remaining on IFX at four time points; before IFX, after induction, at 1 year and at the last follow-up. Response was divided into sustained primary, recovered, durable (combined sustained primary and recovered) and complete LOR (discontinuation from LOR or intolerance). Results: Overall, 28/47 (60%) children sustained primary response over a median duration of 2.83 years (1.6–4.4, IQR). 19/47 (40%) developed LOR (including 2 intolerant) at a median of 11 months (9–19, IQR). Of 17 with LOR, 7 were successfully re-induced giving durable response (35/47, 74%); 6 failed dose intensification needing surgery (n = 2), second anti-TNF (n = 2) or both (n = 2). 4 had surgery without dose intensification. LOR was associated with low BMI at diagnosis, lower height Z scores prior to induction, elevated CRP following induction (p = 0.007) and failure to use concomitant IM (p = 0.02). Conclusion: The cumulative probability of durable response to IFX in luminal CD was 83%, 74% and 70% after 1, 2, and 3 years on IFX maintenance therapy.